A widespread facultative hemi-parasitic weed, threatening rice production in Africa - Rodenburg, J.; Morawetz JJ; Bastiaans, L. (Wiley, 2015)
Rhamphicarpa fistulosa is a facultative hemi-parasitic plant of the Orobanchaceae family, adapted to wet soils. Apart from tropical Australia, it is only found in sub-Saharan Africa, where it is considered a minor weed in cereal crops such as rice. Due to this status, the species has received only sporadic attention. Recent field observations and encounters with rice farmers in several African countries showed that R. fistulosa is, however, a more serious and increasing production constraint than previously thought. Results from a systematic literature review and a global herbarium study support this. The species has a broad distribution over Africa (at least 35 countries from Madagascar to Senegal and from Sudan to South Africa) and a wide range in altitude (0–2150 m a.s.l.) and environment (waterlogged swamps to moist free-draining uplands). Rhamphicarpa fistulosa is relatively independent and persistent because of the presumably wide host range, the facultative nature of its parasitism and its prolific seed (estimated 100 000 seeds m−2 under moderate infestation levels). Finally, R. fistulosa causes severe yield losses (average 60%) and high regional annual economic losses (estimated US $175 million), while effective control options are scant and awareness of the species among important R&D stakeholders is almost absent. An integrated approach is advocated to assist the rice sector to reduce current R. fistulosa-inflicted losses and to prevent further spread of the species into new areas.